The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5455/medscience.2017.06.8628
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of melatonin on acetylsalicylic acid induced liver damage in rats

Abstract: We investigated the effects of acute high doses of acetylsalicylic acid (ASA) on liver tissue and the protective and therapeutic effects of melatonin on ASA related damage. Forty rats were randomly divided into five groups of eight: group 1, control; group 2, administered 200 mg/kg ASA; group 3, administered 5 mg/kg melatonin 45 min before ASA; group 4, administered 5 mg/kg melatonin 45 min after ASA; group 5, administered 5 mg/kg melatonin. We measured malondialdehyde (MDA), superoxide dismutase (SOD), catala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This was compensated by the melatonin administration in the Cast+Mel group. In other studies, melatonin has shown to protect liver against chemical and diet-induced hepatic damages and oxidative stress following ovariectomy [1115]. Castration, as a surgical procedure, induced oxidative stress, inflammation, and long-time adverse effects, which could be reversed by the administration of melatonin [8, 15, 21, 25, 31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was compensated by the melatonin administration in the Cast+Mel group. In other studies, melatonin has shown to protect liver against chemical and diet-induced hepatic damages and oxidative stress following ovariectomy [1115]. Castration, as a surgical procedure, induced oxidative stress, inflammation, and long-time adverse effects, which could be reversed by the administration of melatonin [8, 15, 21, 25, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) is markedly elevated in response to cholestasis. The hepatoprotective effects of melatonin, such as acetylsalicylic acid-induced liver damage in rats [11], rats fed with a high-fat ratio [12], hepatic necrosis in streptozotocin-induced diabetic rats [13], and tramadol-induced hepatotoxicity in albino rats [14], have been confirmed in experimental studies. Oxidative stress and inflammation induced during aging in the liver have been more marked in castrated than in the intact female rats.…”
Section: Introductionmentioning
confidence: 99%